Enhancement of conventional WC-Co and Inconel 625 HVOF thermal spray coatings by the addition of nanostructured WC-Co for wear/corrosion applications in the oil/gas industry. Issue 1 (2nd January 2016) - Al-Hamed, A. A.; Benyounis, K. Y.; Al-Fadhli, H. Y.; Yilbas, B. S.; Hashmi, M. S. J.; Stokes, J.
Abstract: Recently, economical and fast solutions for preventing failure due to wear and corrosion in oil and gas industries have been reduced through the deposition of cermets using HVOF thermal spray coatings especially tungsten carbide–cobalt (Diamalloy 2004) deposits to reduce wear effects and Inconel-625 (Diamalloy 1005) to prevent corrosion. The new research trend towards the development of bimodal (mixed of nano- and micro-size particle) feedstock powders, through the addition of nanostructured WC-Co, is showing promise and is under investigation in this research. A design-of-experiment software was implemented to study the influence of different powder percentage on the coating performance such as coating microstructure and coating mechanical performance, such as three-point bending tests and hardness measurement. Results show that hardness, bending and yield strength of the coating increased as the composition percentage of nanostructured WC-12Co mixed in with the Diamalloy 2004/1005 (WC-12Co micro/Inconel-625, respectively) composite increased due to the strong adhesion of WC nanosize grains at the substrate/coating interface through improved mechanical interlocking and reduce the possibility of cracks initiation. The results show promise in terms of the current maintenance challenges experienced by the oil/gas industry today, in terms of possibly extending the life of components, plus providing huge economic savings.